Light-emitting diode therapy (LEDT) improves functional capacity in rats with heart failure. Issue 5 (July 2016) - Capalonga, Lucas; Karsten, Marlus; Hentschke, Vítor; Rossato, Douglas; Dornelles, Maurício; Sonza, Anelise; Bagnato, Vanderlei; Ferraresi, Cleber; Parizotto, Nivaldo; Dal Lago, Pedro
Abstract The syndrome of heart failure (HF) promotes central and peripheral dysfunctions that result in functional capacity decrease, leading to fatigue, dyspnea, and exercise intolerance. The use of light-emitting diode therapy (LEDT) has shown good results reducing fatigue and exercise intolerance, when applied on skeletal muscles before or after exercises. Thereby, the aim of this study was to compare the effects of LEDT on functional capacity, aerobic power, and hemodynamic function in HF rats. Male Wistar rats (230–260 g) were randomly allocated into three experimental groups: Sham (n = 6), Control-HF (n = 4), and LEDT-HF (n = 6). The animals were subjected to an exercise performance test (ET) with gas analysis coupled in a metabolic chamber for rats performed two times (6 and 14 weeks after myocardial infarction). On the day after the baseline aerobic capacity test, the animals were submitted during 8 weeks to the phototherapy protocol, five times/week, 60 s of irradiation, 6 J delivered per muscle group. Statistical analysis was performed by one- and two-way ANOVAs with repeated measures and Student-Newman-Keuls post hoc tests (p ≤ 0.05). Comparing the percentage difference (Δ) between baseline and the final ET, there was no significant difference for the VO2max variable considering all groups. However, Sham and LEDT-HF groups showed higher relative values than the Control-HF group, respectively, for distance covered (27.7 and 32.5 %), time of exercise test (17.7 and 20.5 %), and speed (13.6 and 12.2 %). In conclusion, LEDT was able to increase the functional capacity evaluated by distance covered, time, and speed of exercise in rats with HF.